Kajian Empiris Perbandingan Biaya Konstruksi Baja dan Beton pada Pembangunan Gedung Fakultas Ilmu Pendidikan Universitas Tribhuwana Tunggadewi Malang - Sabikun, Ahmad; Suhudi; Wijaya, Handika Setya (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2018)
In a construction project on building planning, the selection of materials and materials is very necessary. This is so that the building project can run well, with an efficient cost and can be carried out on time and has the strength to bear the burden on the building. The method to be carried out is an important part of project implementation. The important thing is the coefficient in the execution of work at a lower cost. Determination of the coefficient of work implementation must refer to the Indonesian National Standard (SNI). Steel is a construction material that is resistant to tensile force while concrete is a strong construction material against compressive force. However, of these two materials have different prices, strengths and methods of implementation. Structural analysis in this study uses the staad Pro V8i software to determine internal forces in the structure. In calculating the cost budget analysis used is the analysis of the Ministry of PUPR in 2016. From observations made on the column and beam building construction of the Faculty of Education, University of Tribhuwana Tunggadewi Malang which has a building area of ??205.7 m2 and consists of five floors with a height of 23.08 m by using a steel structure WF (Wide Flange) on the existing building with a total planning cost of Rp 766.560.101,24. While the total cost of planning reinforced concrete as a comparison of the steel structure is worth Rp 449,250,345.85. From the results of data analysis that has been done to find a more economical price is reinforced concrete structure with the difference between the two comparisons is Rp. 317.309.755,39. The savings in the cost of planning work for column structures and reinforced concrete beams reached 37% more economical than steel.